2006
DOI: 10.1128/jvi.80.9.4380-4387.2006
|View full text |Cite
|
Sign up to set email alerts
|

Base Pairing between the 5′ Half of ε and a cis -Acting Sequence, Φ, Makes a Contribution to the Synthesis of Minus-Strand DNA for Human Hepatitis B Virus

Abstract: Synthesis of minus-strand DNA of human hepatitis B virus (HBV) can be divided into three phases: initiation of DNA synthesis, the template switch, and elongation of minus-strand DNA. Although much is known about minus-strand DNA synthesis, the mechanism(s) by which this occurs has not been completely elucidated. Through a deletion analysis, we have identified a cis-acting element involved in minus-strand DNA synthesis that lies within a 27-nucleotide region between DR2 and the 3 copy of DR1. A subset of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…Most of is partially complementary to the 5´ half of ε. Mutations affecting the base-pairing potential between the two sequences can, indeed, influence the efficiency of (-)-DNA synthesis [147] . Exactly how an ε-φ interaction would aid in primer translocation is unclear because base-pairing would simultaneously affect the proper ε structure, implying some temporal regulation.…”
Section: ( + ) -S T R a N D D N A S Y N T H E S I S A N D Circularizamentioning
confidence: 99%
See 1 more Smart Citation
“…Most of is partially complementary to the 5´ half of ε. Mutations affecting the base-pairing potential between the two sequences can, indeed, influence the efficiency of (-)-DNA synthesis [147] . Exactly how an ε-φ interaction would aid in primer translocation is unclear because base-pairing would simultaneously affect the proper ε structure, implying some temporal regulation.…”
Section: ( + ) -S T R a N D D N A S Y N T H E S I S A N D Circularizamentioning
confidence: 99%
“…via elongation initiation factor 4G (eIF-4G; large oval). More specifically, ε might base-pair with φ [146,147] , as indicated by the grey arrows. In such an arrangement, a small movement, rather than a big jump, of TP with the bound DNA primer (dashed outline) would suffice for specific translocation to DR1*.…”
Section: Dna Primer Translocation and (-)-Dna Completionmentioning
confidence: 99%
“…6d). Recent studies have shown that mutation of the lower bulge of the e structure (1858-1863) prevents the pol-e interaction (Abraham & Loeb, 2006;Oropeza & McLachlan, 2006). We co-transfected eGFP-pol and core with a vector expressing e mutated in this fashion (ppreC-/C e mutant) and found that core localized in the nucleus (Fig.…”
Section: Cytoplasmic Core Localization Requires Pol and Ementioning
confidence: 99%
“…1B) (48,53,62,64). The specificity of this template switch is determined by base pairing between nucleotides in ε and nucleotides flanking the acceptor site ( and ) (2,3). Subsequently, the minus-strand DNA is elongated to produce a full-length minus-strand DNA [(Ϫ)DNA elongation] (Fig.…”
mentioning
confidence: 99%